L’évaluation, un outil de l’ergonome pour transformer le contexte d’intervention - Aurélie Landry; Arnaud Tran Van (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article presents the application of action-research whose aim is to investigate whether an evaluative research type process can identify favorable factors for an intervention and allow evaluation of the stakeholders’ hypotheses on the links between the intervention process and the results obtained. The cases used illustrate how evaluative research can help the ergonomist improve the conditions in which he acts by sharing evaluation indicators on the project process. By communicating intervention process indicators with the other stakeholders, the ergonomist changes the context in which he acts during the intervention. By also using result indicators, the ergonomist can show the contribution of the intervention and attempt to better adapt his methods, considering the advantages or obstacles present in the context of the intervention.